A literature study on Arsenic Compounds - Cho, Tae-Sung; Seo, Jung-Chul; Son, In-Suk; Kwon, Hae-Yon; Youn, Hyoun-Min; Jang, Kyung-Jeon; Song, Choon-Ho; Ahn, Chang-Beohm; Kim, Ok; Choe, Seong-Mo; Gwon, Gi-Rok (Korean Pharmacopuncture Institute, 2002)
Objective: The purpose of this study is to develop and activate the methods of using the arsenic compounds as the anti-cancer medicine. Methods: We investigated some literatures on the using methods, the effects for anti-cancer, and the toxicity of the arsenic compounds. Results: The results are summarized as follows. 1. As is the one of the nitrogen familIy(5A familly). 2. The Arsenic compounds which have been used as the one of the oriental medicine are the Arsenicum Sulbimatum(A52O3) and the Realgar(AsS). 3. As+ 3 is more toxic than the other arsenic compounds. The fatal amount is 100-300 mg. So, it is used 1-5 mg/day as a medicine. 4. The Arsenicwn Sulbimatum(A52O3) and the Realgar(AsS) are used after the heat treatment or the boiling with the acetic acid. 5. The gastrointestinal tract, vessel, and respiration are affected by the acute toxicity of the arsenic compounds. 6. The arsenic compounds are good for the dermatosis and the malignant cancer, especially the acute promyelocytic leukcrnia(APL). we should study the reason of these and the different effect in concentration, also develop new methods of using the the arsenic compounds as getting rid of their toxicity.